2019
DOI: 10.24983/scitemed.aohns.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Juxtacortical Chondrosarcoma: A Systematic Review

Abstract: Objective: To present a case and systematically evaluate trends in clinical presentation, imaging, histopathology, and management modalities and outcomes of all head and neck juxtacortical chondrosarcoma (HNJCS) cases reported in the existing literature. Methods: We describe a rare case of HNJCS from our tertiary referral center following which the PubMed, MEDLINE, Embase, and Web of Science databases were searched for all HNJCS reports. Relevant titles and abstracts were screened. Resulting full-text articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…The most frequently involved anatomical structure was identified as the cricoid cartilage, and dyspnea, hoarseness and the sensation of mass in the throat were the most frequently reported symptoms. The surgical technique and the degree of histological differentiation were factors correlated with the prognosis [22]. In another systematic review that included only nine cases reported from 1946 to 2019, Jones and collaborators found a relatively low rate of loco-regional recurrences with only one of these cases recurring 4 years after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently involved anatomical structure was identified as the cricoid cartilage, and dyspnea, hoarseness and the sensation of mass in the throat were the most frequently reported symptoms. The surgical technique and the degree of histological differentiation were factors correlated with the prognosis [22]. In another systematic review that included only nine cases reported from 1946 to 2019, Jones and collaborators found a relatively low rate of loco-regional recurrences with only one of these cases recurring 4 years after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%